Characterization of the Mycovirome from the Plant-Pathogenic Fungus Cercospora beticola - Yingxi Li; Mengke Zhou; Yizhou Yang; Qi Liu; Zongying Zhang; Chenggui Han; Ying Wang (Viruses, 2021)
Cercospora leaf spot (CLS) caused by Cercospora beticola is a devastating foliar disease of sugar beet (Beta vulgaris), resulting in high yield losses worldwide. Mycoviruses are widespread fungi viruses and can be used as a potential biocontrol agent for fugal disease management. To determine the presence of mycoviruses in C. beticola, high-throughput sequencing analysis was used to determine the diversity of mycoviruses in 139 C. beticola isolates collected from major sugar beet production areas in China. The high-throughput sequencing reads were assembled and searched against the NCBI database using BLASTn and BLASTx. The results showed that the obtained 93 contigs were derived from eight novel mycoviruses, which were grouped into 3 distinct lineages, belonging to the families Hypoviridae, Narnaviridae and Botourmiaviridae, as well as some unclassified (−)ssRNA viruses in the order Bunyavirales and Mononegavirales. To the best of our knowledge, this is the first identification of highly diverse mycoviruses in C. beticola. The novel mycoviruses explored in this study will provide new viral materials to biocontrol Cercospora diseases. Future studies of these mycoviruses will aim to assess the roles of each mycovirus in biological function of C. beticola in the future.